Pengaruh Pelaksanaan Supervisi Pendidikan Oleh Kepala Sekolah Terhadap Kinerja Guru di Mts Al-Munawwarah Binjai Utara - Alfi Hafifah Habibah; Ayu Putri Julia; Hafni Lativah; M. Solih; Ryan Fazli Zulna; Inom Nasution (Universitas Maritim AMNI Semarang, 2023)
This journal is conducted with research, which aims to determine and define how the effect of the implementation of educational supervision by the principal on teacher performance in schools. This research was conducted using one approach, namely qualitative approach. The educators in schools became the subject of research by taking samples of several teachers, using proportional random sampling techniques, and from the research and assessment it can be seen that the implementation of educational supervision by the principal has a positive effect on teacher performance and the implementation of educational supervision by the principal is also very impactful on teacher performance in schools.